Analisis Keterampilan Proses Sains Siswa SMP Imam Nawawi: Analysis of Science Process Skills of Imam Nawawi Junior High School Students - Rahmatullah (Aisha Edutama, 2024)
Science process skills are one of the most important skills for students to have, one of which is students at Imam Nawawi Middle School. This research uses quantitative descriptive methods to reveal the science process skills of Imam Nawawi Middle School students where the research subjects were 55 students in the 2023/2024 academic year. The results of the research show that students' science process skills in the indicators of observation, grouping, designing experiments and communication obtained results in the medium category, while the hypothesis indicators were in the low category. These findings indicate that there is a need for innovative steps in improving students' science process skills at Imam Nawawi Middle School.